SYSTEMATIC REVIEW ON THE MEDICAL PRACTITIONER'S KNOWLEDGE ABOUT THERADIOLOGY EXAMINATION AND POSITIVE INFLUENCE OF RADIATION TRAINING - MR. SURESH SUKUMAR,; DR. RAJAGOPAL K. V,; DR. SABU K M,; MR.GURUPRASAD.V,; MRS. KR. BANUMATHE, (International Journal of Pharma and Bio Sciences, 2016)
The aim of this systematic review is to search for all available publications on surveys assessing medical practitioner’s knowledge on radiation doses and radiation risks of radiology examination. Acochrane systematic review was performed using four databases.211 reference were found. Only primary studies assessing the medical practitioner’s knowledge on radiation doses and radiation risks of radiology examination were included The outcome of the systematic literature shows that only a minority of medical practitioner were well informed about these topics in almost all studies we found. However the different methodologies of the 17 included studies render an interpretation difficult. Nevertheless, this systematic review implies that radiation protection awareness among physicians particularly for patient medical practitioner could be improved. The review did not asses the studies by a quantitative and qualitative synthesis, which could have helped in scoring the studies on the basis of the indicators.